P-doped PANI/AgMWs nano/micro coating towards high-efficiency flame retardancy and electromagnetic interference shielding. (1st June 2022) - Zhang, Lin; Liu, Bo-Wen; Wang, Yu-Zhong; Fu, Teng; Zhao, Hai-Bo
Abstract: With the rapid development of 5G technology, functional coatings with both high-efficiency flame retardancy and electromagnetic interference shielding (EMI) are urgently needed, while traditional inefficient methods have encountered bottlenecks. Herein, we demonstrate an eco-friendly and multifunctional nano/micro coating constructed by biomass phytic acid (PA) induced polymerization and self-assembly of polyaniline (PANI) nanoparticles and dip-coating of silver microwires (AgMWs). In this design, PA with high flame-retardant efficiency is smartly doped into PANI to achieve P-N synergistic flame retardancy and improve electrical conductivity of PANI simultaneously. Consequently, under the coaction of AgMWs, P-doped PANI nanoparticles, as well as unique continuous micro-nano structures, the nano/micro coating can endow commercial polyurethane (PU) foams with outstanding EMI shielding performance (∼51 dB in X-band). Meanwhile, the coated PU foam exhibits high flame retardancy due to the P-N synergistic effect of PA/PANI, which self-extinguishes immediately after ignition during the UL-94 vertical burning test, shows a high limiting oxygen index (LOI) value of 34.8%, and exhibits a 50.7% lower peak heat release rate compared with pure PU foam. Further, the functional nano/micro coating with three-dimensional and highly porous structure makes the foam thermally insulating and infrared stealthing. The eco-friendliness and simplicity of this method and its successful application in commercial PU foam make it potentially applicable for the preparation of various kinds of multifunctional EMI shielding materials. Graphical abstract: Image 1 Highlights: A multifunctional coating was constructed via the PA-induced polymerization and self-assembly of polyaniline nanoparticles. The conductive coating endowed the PU foam with an EMI SE value of 51 dB in X-band. High flame retardancy and low heat release were realized by the phosphorus-containing coating. The EMI shielding and flame-retardant mechanism were comprehensively investigated.